The Mediating Effect of Organizational Culture on the Relationship between Leadership Style and Organizational Learning in Iraqi Universities - Ali Husien, Wesam; Noori Alhamdany, Saba; Mahmood Khalaf ALSabawy, Mushtak (International Journal of Psychosocial Rehabilitation, 2020)
Leadership style is known as a power that affects followers, especially transformational and transactional leadership, which is highlighted as an important leadership style. However, transactional leadership is considered a second level while transformational leadership is a first level in terms of the power effect on followers. For both leadership styles, organizational learning is one of the problematic issues that stands critically for leaders, and they have to decide about it. This research studies the effect of transformational and transactional leadership and compares their effects on organizational learning. However, examining the effect of leadership style on organizational learning is not a new research scope, and the recent research findings have variable findings. Therefore, this research used the organizational culture as a mediating culture between leadership style and organizational learning. This search was run based on an individual analysis and used the private university in Iraq-—Baghdad city. The collected data were among all the private universities using a handed or administrative questionnaire. Moreover, structural equational modeling is used for data analysis. The findings were impressive and brought new knowledge to the knowledge that transactional leadership has a more powerful effect on organizational learning than transactional leadership, and the organizational culture played a vital role in improving the organizational learning.